KEKUATAN KETERANGAN SAKSI ANAK DALAM PENEGAKAN HUKUM PADA KASUS TINDAK PIDANA ASUSILA TANPA DIDUKUNG ALAT BUKTI LAINNYA - Putri Sasbita Aqila; Mukhlis R; Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The evidentiary stage is one of the aspects of the trial, especially in the aspectof evidence that plays a role in proving a person's guilt so that he can besentenced by a judge. In this case, many children are victims as well as witnessesin cases of immoral crimes by giving testimony under oath, this is not inaccordance with the Criminal Procedure Code which requires every witness to besworn in, but over time the issuance of the latest regulations, namely the Law onSexual Violence, this is certainly a problem for judges where children are the onlywitnesses who hear, see, and experience an immoral crime themselves.The objectives of writing this thesis are: first, whether the child's testimonycan be taken into consideration by the judge in making a decision on an indecentcrime case. Second, What is the strength of child witness testimony in court,without the support of other evidence in several cases.This type of research can be classified as normative juridical research,because in this research the author uses literature study materials such as officialdocuments, books to conduct research in this study, data sources used, primarydata, secondary data and tertiary data, collection techniques in this research withliterature review methods or documentary studies.From the results of this study it can be concluded First, the testimony of childwitnesses who cannot be given under oath, is not valid evidence, but can be usedas a clue and can prove that the defendant is guilty if accompanied by 1 (one)other valid evidence and the judge gains confidence in the case this is stated inarticle 25 paragraph 1 of the TPKS Law. Second, the testimony of child witnesseswithout oath that is used as a clue is based on the correspondence with otherevidence that is considered by the judge in imposing sexual crimes on children.The author's suggestions, First, it is hoped that judges who try criminal cases,especially in examining and evaluating the testimony of minor witnesses, must bewise and wise. Second, there needs to be an internal judicial regulation thatdedicates the judge's belief in the consideration of child witness testimony byfollowing the latest regulations and closing the gap so that cases of immoralviolence decrease significantly with a deterrent effect for the defendants. Eitherthrough the decision of the Supreme Court in order to increase the evidentiarypower of child witness testimony in order to achieve the legal objectives of justice,certainty and expediency.Keywords: Strength of Proof - Indecent Crimes - Child Witnesses